2017
DOI: 10.1186/s12893-016-0186-6
|View full text |Cite
|
Sign up to set email alerts
|

Albumin and surgical site infection risk in orthopaedics: a meta-analysis

Abstract: BackgroudSurigical site infection has been a challenge for surgeons for many years, the prevalence of serum albumin <3.5g/dL has been reported to be associated with increased orthopaedic complications. However, the prognostic implications and significance of serum albumin <3.5g/dL after orthopaedic surgeries remain ambiguity. In this study, we performed a meta-analysis to access the predictive value of serum albumin level on SSI.MethodsA basic data search was performed in PubMed and Web of Science, in addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 30 publications
4
84
0
1
Order By: Relevance
“…The lower albumin as a significant risk factor for DSSI after ankle fracture was first reported in this study, although it had been reported as risk factors for other complications or SSIs after other orthopaedic surgeries, like spine fusion, hip arthroplasty, and hip fractures. [22][23][24] Yuwen et al 25 conducted a meta-analysis of 13 studies including 112 183 patients with orthopaedic surgeries and concluded that preoperative albumin <35 g/L increased the SSI risk by 2.39 times, compared with those with albumin >35 g/L. In addition, lower albumin had been established as an increased risk of poor outcome of infection, 26 postoperative death, 27 and prolonged total hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…The lower albumin as a significant risk factor for DSSI after ankle fracture was first reported in this study, although it had been reported as risk factors for other complications or SSIs after other orthopaedic surgeries, like spine fusion, hip arthroplasty, and hip fractures. [22][23][24] Yuwen et al 25 conducted a meta-analysis of 13 studies including 112 183 patients with orthopaedic surgeries and concluded that preoperative albumin <35 g/L increased the SSI risk by 2.39 times, compared with those with albumin >35 g/L. In addition, lower albumin had been established as an increased risk of poor outcome of infection, 26 postoperative death, 27 and prolonged total hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…These are all markers of both, malnutrition and SSI, alike. In future trials, we 75 would also need to consider not only gross protein and carbohydrate intake but also (and 76 perhaps especially) micronutrients [1,8]; and perhaps to concentrate on nutritional status 77 independently of confounders such as diabetes and high alcohol intake, gastrointestinal 78 disease and immune-suppression. Accepting that these are important, any proposed trial to 79 determine whether preoperative nutritional optimization might be more feasible without…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In reality, available It might be that the value of the current diagnostic schema for malnutrition may lie 55 essentially in identifying sicker patients. To cite a frequent example, most author groups use 56 hypoalbuminemia with a cut-off of 3.5 g/dL [1,7,8] as the most important marker for 57 malnutrition. However, although albumin may be a reliable serum marker of chronic 58 nutritional status, it is not specific, in that inflammation or stress may also cause 59 hypoalbuminemia without associated malnutrition [1].…”
mentioning
confidence: 99%
“…Nutritional factors have been related to the incidence of SSI in many surgical procedures, among which are underweight, obesity, and low serum albumin. 8,[13][14][15] The majority of the patients studied had a normal body mass index with a relatively low frequency of obesity (8.9%). The diversity of the nutritional habits and the socioeconomic characteristics (mainly expatriate population with low…”
Section: Discussionmentioning
confidence: 99%